1987
DOI: 10.1007/bf00302389
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Prudhoe Bay crude oil and its aliphatic, aromatic and heterocyclic fractions in inducing mortality and aryl hydrocarbon hydroxylase in chick embryo in ovo

Abstract: Prudhoe Bay crude oil (PBCO) and its aliphatic, aromatic and heterocyclic fractions were tested on the developing chick embryo for (i) embryotoxicity (ii) their ability to induce hepatic and renal cytochrome P450 levels as well as hepatic, renal and pulmonary aryl hydrocarbon hydroxylase activities. On the basis of its concentration in PBCO, the aromatic fraction was responsible for most of the embryotoxicity as well as for the enzyme inducing ability. The NOS fraction constituted less than 7% (w/v) of PBCO bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…Laboratory studies have also demonstrated a relationship between cytochrome P450 induction and PAHs. Cytochrome P450 induction was correlated with PAHs in the chicken embryo [8] and herring gull [9]. A variety of PAHs injected into chicken embryos induced cytochrome P450 activity [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies have also demonstrated a relationship between cytochrome P450 induction and PAHs. Cytochrome P450 induction was correlated with PAHs in the chicken embryo [8] and herring gull [9]. A variety of PAHs injected into chicken embryos induced cytochrome P450 activity [10].…”
Section: Discussionmentioning
confidence: 99%
“…Trace element concentrations in soil and small mammals were higher at sites treated with petrochemical waste compared to reference sites [7]. Induction of hepatic monooxygenase activity after exposure to PAHs has been documented in birds in both the laboratory [8–11] and the field [12].…”
Section: Introductionmentioning
confidence: 99%
“…Other crude oils, such as Kuwait crude, are also able to induce BPH activity in the liver, kidney, and SI of rats (10). We have shown that the aromatic fraction of PBCO is primarily responsible for induction of hepatic BPH activity in the developing chick embryo (6). It is likely that these same components are responsible for BPH induction in the liver and SI of rats.…”
Section: Discussionmentioning
confidence: 96%
“…Proportional compositions of AHs were more evenly distributed at both Sand Point and Coal Harbor, where similar AH compounds comprised 5% or more of the AHs. Although highly correlated with PAHs, AHs apparently do not induce P4501A [34,35].…”
Section: Discussionmentioning
confidence: 99%